Ultrazvukový staging časných stadií karcinomu endometria, analýza vlastního souboru za období let 2012-2016 - Míka, O; Kožnarová, J; Sak, P (Ceska gynekologie, 2017)
OBJECTIVE: The aim of the presented study was to evaluate the accuracy of ultrasound staging of early stage endometrial cancer depending on grading, evaluation of ultrasound examination accuracy growing overtime with gained experience of examiners and comparison of subjective versus objective modalities of deep myometrial invasion assessment in the file of patients who were referred in The Oncogyneacologic Center, Department of Gyneacology and Obstetrics in České Budějovice. DESIGN: Retrospective study. SETTINGS: Department of Gyneacology and Obstetrics, Hospital České Budějovice a.s.Methods and the file: In this arcticle we retrospectively evaluate the file of 136 patients with early stage endometrial cancer. The patients underwent diagnostic and therapeutic procedures during the years 2012-2016 in our department. All these patients were able to be compared in different aproaches to deep myometrial invasion assessment using ultrasound examination. RESULTS: Comparing the used methods of deep myometrial invasion assessment with ultrasound examination of early stage endometrial cancer patients the examiner's subjective evaluation seems to be the best approach. After the first year of doing these assessments sensitivity performed 80%, specificity 79% and infiltration of cervix sensitivity 70% and specificity 99%. In case the patients were divided into groups according to the grading, low grade assessed worst sensitivity 64% (high grade l00%), but the best specificity 75% (high grade 56%). The evaluation of objective approaches of ultrasound assement with used cut offs performed the best sensitivity 81% tumour free minimal margin (specificity 67%). On the contrary the best specificity 90% performed the ratio AP (anteroposterior) diameter tumour/AP diameter uterine (senzitivity 54%). CONCLUSION: Generally in oncological therapy the most important things to put stress on the very accurate staging of oncological disease. In oncogyneacology ultrasound becomes more and more required examination. In our file we proved the significance of ultrasound examination in diagnostics and staging of endometrial cancer and we also proved that the accuracy level in early stage depends on the examiner´s experience. After one year practice our results reach the level of the results presented globally, no matter which of the methods - ultrasound MRI or frozen section - was used.
Keywords: Predictive Value of Tests; senzitivita a specificita; Neoplasm Staging; nádory endometria; Retrospective Studies; lidé; invazivní růst nádoru; Humans; retrospektivní studie; prediktivní hodnota testů; Ultrasonography; early stages; Neoplasm Invasiveness; Sensitivity and Specificity; ultrasonografie; myometrium; staging nádorů; Myometrium; zmrazené řezy; ultrasound examination staging.; endometrial cancer; ženské pohlaví; Endometrial Neoplasms; Female; Frozen Sections